Relative effects of pre- and post-eruption water fluoride on caries experience by surface type of permanent first molars - Singh KA, Spencer AJ. (Blackwell Synergy, 2004)
To determine the relative pre- and post-eruption exposure effects of fluoridated water on the caries experience of different surface types of first permanent molars.